2019
DOI: 10.1680/jgele.18.00191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of installation method on static lateral response of displacement piles in sand

Abstract: The influence of the installation method on the static lateral response of displacement piles is presented using the results from reduced-scale field tests on piles in medium dense siliceous sand. In contrast to the importance of the installation method on shaft friction, it is shown that lateral response of piles to static lateral loading is largely insensitive to the installation method. The tests show that the lateral responses of impact-driven piles with different installation frequencies and jacked piles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This explains why in the numerical analyses reported in (Le et al, 2021) vibratory driven piles are reported to show a lower accumulation of deformation compared to impact driven piles, since the simulation of the installation has been performed ideally drained. Similarly, a higher stiffness to lateral monotonic loading of vibratory driven piles compared to impact driven piles observed in the field test campaign reported in (Anusic et al, 2019) can be explained by the stronger compaction occurring without the presence of pore water.…”
Section: Numerical Model For the Lateral Loadingmentioning
confidence: 67%
See 2 more Smart Citations
“…This explains why in the numerical analyses reported in (Le et al, 2021) vibratory driven piles are reported to show a lower accumulation of deformation compared to impact driven piles, since the simulation of the installation has been performed ideally drained. Similarly, a higher stiffness to lateral monotonic loading of vibratory driven piles compared to impact driven piles observed in the field test campaign reported in (Anusic et al, 2019) can be explained by the stronger compaction occurring without the presence of pore water.…”
Section: Numerical Model For the Lateral Loadingmentioning
confidence: 67%
“…In contrast to these studies, another recent field test campaign found that vibratory driven piles had a slightly higher resistance to lateral monotonic loading than impact driven piles (Anusic et al, 2019). It was hypothesised that the higher resistance was due to greater compaction of the soil caused by vibratory driving.…”
Section: Response Of Vibratory Driven Piles To (Cyclic) Lateral Loadingmentioning
confidence: 88%
See 1 more Smart Citation
“…As a common form of foundation, the research on the fabrication, installation and vertical-bearing capacity of pile foundations is very rich [1,2]. However, pile foundations are often subjected to irregular horizontal dynamic loads, such as vibrational loads caused by ground motions and wind loads [3][4][5][6][7]. Therefore, the dynamic stability of these pile foundations needs to be solved when they are subjected to lateral loads, such as seismic forces.…”
Section: Introductionmentioning
confidence: 99%
“…stricter environmental regulations in terms of underwater noise levels has motivated the development of alternatives to the conventional impact-driving method of monopile installation. One of the alternatives is the (axial) vibratory installation, which has been previously studied in field [1,2,4] and laboratory [3,5] conditions. However, there is limited knowledge on the effects of vibratory installation (and how these effects differ from those caused by impact-driving) on the lateral response of monopiles.…”
mentioning
confidence: 99%